2018
DOI: 10.1016/j.jid.2017.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide DNA Methylation Profiling Identifies Differential Methylation in Uninvolved Psoriatic Epidermis

Abstract: Psoriasis is a chronic inflammatory skin disease with both local and systemic components. Genome-wide approaches have identified more than 60 psoriasis-susceptibility loci, but genes are estimated to explain only one-third of the heritability in psoriasis, suggesting additional, yet unidentified, sources of heritability. Epigenetic modifications have been linked to psoriasis and altered DNA methylation patterns in psoriatic versus healthy skin have been reported in whole-skin biopsies. In this study, focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…1d). We also validated the methylation values of these regions by using published DNA methylome data [8, 37, 38]. The results showed that these dmCGCGCGGs in cfDNA have a median methylation level of 42% in the liver, which is considerably higher than that in the seven other tissues ( P < 0.01, two-tailed MWW test, Fig.…”
Section: Resultsmentioning
confidence: 80%
“…1d). We also validated the methylation values of these regions by using published DNA methylome data [8, 37, 38]. The results showed that these dmCGCGCGGs in cfDNA have a median methylation level of 42% in the liver, which is considerably higher than that in the seven other tissues ( P < 0.01, two-tailed MWW test, Fig.…”
Section: Resultsmentioning
confidence: 80%
“…The hypomethylated CpG site linked to LOC730668, which is a Dynein Heavy Chain-Like pseudogene located on chromosome 22, has been reported in two different studies to be differentially hypomethylated in individuals with temporal lobe epilepsy, and in individuals with psoriatic epidermis [60,61] Building a prediction model for use in forensic investigations requires a small number of markers due to the minute quantities of DNA that is frequently recovered from forensic samples [64]. The six AR CpG sites selected by stepwise regression, which contained only one CpG marker that was newly added to the EPIC BeadChip, had a MAD value of 4.6 years based on the validation set.…”
Section: B)mentioning
confidence: 98%
“…In addition to different patterns of MHC class I expression, psoriasis patients display distinct gene expression signatures and DNA methylation profiles in non-lesional skin. 88,89 Keratinocytes from non-lesional psoriasis skin also exhibit functional differences with decreased triggering of IRF-1 and STAT1 following exposure to IFN-γ. 90 In line with decreased IFN-γ responses, supernatants from activated lesional T cells led to increased proliferation 91 and resistance against UV-induced apoptosis than healthy counterparts.…”
Section: Keratinocytes and Cytokines: A Miscommunication?mentioning
confidence: 99%